Vibrio parahaemolyticus: spread, detection and identification techniques - G. S. Skitovich; N. B. Shadrova; O. V. Pruntova (Ветеринария сегодня)
Vibrio parahaemolyticus are gram-negative halophilic bacteria found in marine and coastal waters all over the world which cause acute food-borne gastroenteritis in humans. Rarely V. parahaemolyticus cause wound infections, infections of ears or sepsis in individuals with a compromised immune system. More than 80 serotypes were described worldwide based on antigenic properties of the somatic (0) and capsular (K) antigens. V. parahaemolyticus are characterized by two factors of virulence: thermostable direct hemolysin (tdh), a protein which facilitates the invasion of the human body by the bacterium, and aTDH-related hemolysin (trh) which plays the sameas TDH role in the disease pathogenesis. Most V. parahaemolyticus strains isolated from the environment or sea products in comparison to clinical strains do not produce any thermostable direct hemolysin (TDH) or TDH-related hemolysin (trh). The paper presents V. parahaemolyticus biological properties, pathogenesis peculiarities, their spread and detection techniques.